ANALISIS KEPUASAN DAN LOYALITAS MAHASISWA TEKNIK INFORMATIKA DENGAN PENDEKATAN STRUCTURAL EQUATION MODELING BERDASARKAN PENERAPAN SERVQUAL - Nurfaisal, Yusmedi (Performance, 2014)
This study, entitles "The Satisfaction and The Loyalty Analysis of InformaticsEngineering Student With Structural Equation Modeling Approach Based on the Application of SERVQUAL". The purpose of this study was to determine students satisfactionand loyalty with a Structural Equation Modeling approach based on SERVQUAL application. Researchers decided to take a sample of 100 respondents. SEM analysis wasused to test the model. The results showed that tangibility, reliability, responsiveness,assurance and empathy had a significant positive effect on the satisfaction of student ofinformatics engineering. The satisfaction of students had a significant positive effect onthe loyalty of student of informatics engineering STMIK Amikom Purwokerto.